Determinan Partisipasi Petani Kopi dalam Standar dan Sertifikasi Berkelanjutan Common Code for Coffee Community (4C) - Muhammad Ibnu (Jurnal Tanaman Industri dan Penyegar, 2019)
Sustainable standards and certification can encourage coffee farmers to adopt good agricultural practices (GAP), achieving coffee production that is economically, socially and environmentally sustainable. The Common Code for Coffee Community (4C) is a standard and certification scheme currently exists in Robusta coffee production center in Lampung Province. However, sustainable standard and certification become less relevant without farmers’ participation. Farmers’ participation in standards and certification has been relatively low and studies on the issue are relatively rare. This study aims to analyze the determinants of farmer’s participation in 4C Standards and Certification. The study was conducted in West Lampung and Tanggamus Ragency, Lampung Province from February to May 2019. The total number of respondents was 120 people (4C certified farmers and non-certified farmers) surveyed with a systematic-random-sampling method. Data was analyzed using heckprobit regression. The results showed that farmer participation in 4C was determined by the selling price of coffee, farmers’ side job, farmers' preference to replace coffee with other commodities, and the farmers’ group activity. The results indicated that 4C and coffee stakeholders at national scale need to consider policies on how to improve coffee price, optimizing the farmer organizations, and the added-value of coffee production.